Study on the Synthesis of 6-Hydroxyhexyl 5-(Hydroxymethyl) Furan-2-Carboxylate from 5-Hydroxymethylfurfural (HMF) and Alkanediols - Vu, Trung Nam; Nguyen, Duy Hieu; Nguyen, Tuong Huy; Tran, Thi Thuy; Tran, Thuong Quang; Tran, Quang Tung (JST: Engineering And Technology For Sustainable Development, 2021)
Nowadays, due to the fact that the term ‘sustainable development’ has caught everyone’s attention, chemists have been researching substances which obtainable via synthesizing biocompounds. Recently, scientists found out that 5-hydroxylmethylfurfural (HMF), which can be synthesized via dehydration reaction of common biocompounds like polysaccharides, has a great potential of forming novel derivatives to utilize in the biopolymer manufacturing field. HMF oxidative esterification is one of the notable reactions of which the outcome seems promising and applicable. In this research, the esterification of HMF and hexane-1,6-diol took place directly in DMSO or TEA solvent using Ru/C, Co3O4-N@C as catalysts, base K3PO4; with oxygen 1 bar as an oxidant. LC-MS/MS analysis was used to detect the presence of the ester products; however, due to the low conversion and selectivity, the content of desired product is not enough to isolate and confirm its structure.